(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Herbs are an essential component of the healthcare system in Ayurvedic medicine. In addition to being used in medicine, herbs are also utilized to make a variety of cosmetics and colours as well as to enhance one’s appearance. The purpose of this research is to prepare polyherbal hair oil using plant-based ingredients which are fresh leaves of various plants. Polyherbal hair oil prepared by using multiple herbal components some of containing leaves, roots or whole plant. Firstly all raw materials are characterized by different parameters such as ash values, water and alcohol soluble extractives, TLCs, and phytochemical analysis, etc. Then prepared herbal oils were subjected to General characterization like sensitivity, Grittiness, sedimentation and Physical evaluation such as pH, acid value, viscosity, saponification value, specific gravity, density and stability study. The above parameters were found to be good and within standards. The characterization of all raw materials shows the different parameters and phytochemical analysis of phytoconstituents which are required for healing different hair problems. This is FDA approved herbal hair oil and it s already in use for a patients and it shows very good effect against all hair problems. Conclusively, combination of effective herbs could be used to improve hair growth, nourishes the scalp and prevents dandruff.